Functional screening identifies aryl hydrocarbon receptor as suppressor of lung cancer metastasis - Nothdurft, Silke; Thumser-Henner, Clotilde; Breitenbücher, Frank; Okimoto, Ross A.; Dorsch, Madeleine; Opitz, Christiane; Sadik, Ahmed; Esser, Charlotte; Hölzel, Michael; Asthana, Saurabh; Forster, Jan; Beisser, Daniela; et al. (Oncogenesis, 2020)
Lung cancer mortality largely results from metastasis. Despite curative surgery many patients with early-stage non-small cell lung cancer ultimately succumb to metastatic relapse. Current risk reduction strategies based on cytotoxic chemotherapy and radiation have only modest activity. Against this background, we functionally screened for novel metastasis modulators using a barcoded shRNA library and an orthotopic lung cancer model. We identified aryl hydrocarbon receptor (AHR), a sensor of xenobiotic chemicals and transcription factor, as suppressor of lung cancer metastasis. Knockdown of endogenous AHR induces epithelial-mesenchymal transition signatures, increases invasiveness of lung cancer cells in vitro and metastasis formation in vivo. Low intratumoral AHR expression associates with inferior outcome of patients with resected lung adenocarcinomas. Mechanistically, AHR triggers ATF4 signaling and represses matrix metalloproteinase activity, both counteracting metastatic programs. These findings link the xenobiotic defense system with control of lung cancer progression. AHR-regulated pathways are promising targets for innovative anti-metastatic strategies.